Experimental philosophy. [article]. - Knobe, Joshua
Experimental philosophy is a new interdisciplinary field that uses methods normally associated with psychology to investigate questions normally associated with philosophy. The present review focuses on research in experimental philosophy on four central questions. First, why is it that people's moral judgments appear to influence their intuitions about seemingly nonmoral questions? Second, do people think that moral questions have objective answers, or do they see morality a fundamentally relative? Third, do people believe in free will, and do they see free will as compatible with determinism? Fourth, how do people determine whether an entity is conscious? - (from the authors)